Co-movements of REIT indices with structural changes before and during the subprime mortgage crisis: evidence from Euro-Med markets - Mandaci, Pinar Evrim; Aktan, Bora; Cagli, Efe Çaglar (International Journal of Strategic Property Management, 2014)
This paper examines the long-run relationships between the REIT indices of the UK, Turkey and Israel in the Euro-Med zone with that of MSCI US REIT Index by using weekly data over the period 2003Q3 through 2009Q3, which includes the latest US subprime mortgage crisis and its effects on global stock markets. Although our EG test results do not indicate a long-run relationship, after taking account of the structural changes by applying the GH test, we find a long-run interaction between the REIT indices of UK and Israel with that of the US. However, our results indicate the lack of co-movement between REIT index of Turkey with the US. In addition, our dynamic OLS test results indicate a perfect relationship between the UK and the US indices. Our findings show that international investors who make long-term investments can only gain from diversifying into the real estate market of Turkey among the involved markets in the Euro-Med zone. First Publish Online: 21 Mar 2014